Trajetória política de D. Maria I: ideias ilustradas, convulsão política e melancolia - Abenassiff, Ana Lucia de Souza (2018)
Between 1777 and 1792, Portugal was ruled by the first woman regent on the Portuguese throne: D. Maria I. More quoted than studied, there are many gaps in the trajectory of D. Maria and even on her government. The central objective of this work was to reflect on the complex relations between the private and public life of the monarch and its unfolding. Because it was a biographical analysis, it was necessary to seek subsidies that also shed light on personal aspects, allowing the character to be de-sacralized. The sources collected for the execution of the proposal had different character: personal letters and of government, official documentation and memories produced in the Marian period. Because they are plural sources, we try to look at the different literary genres, the authorship, the context of production of the documents and the possible purposes of their production. On the other hand, we seek to established dialogues with the historiography produced on the theme and its surrounding. We believe that the contribution of this study is to revisit the historiographic debate about Marian government, often presented as obscure and retrograde, as opposed to the information gathered in the sources and the most current perspectives on the subject